Altered glutamatergic tone reveals two distinct resting state networks at the cellular level in hippocampal sclerosis - Jyotirmoy Banerjee (Nature Portfolio, 2017)
Abstract Hippocampal sclerosis (HS), the most common subset of drug-resistant epilepsy (DRE), is associated with large-scale network abnormalities, even under resting state. We studied the excitatory postsynaptic currents (EPSCs) recorded from pyramidal neurons in resected samples under resting conditions from the hippocampal and anterior temporal lobe (ATL) obtained from patients with HS (n = 14) undergoing resective surgery. We observed higher frequency and amplitude of spontaneous EPSCs in both the samples compared to non-seizure control samples. Application of tetrodotoxin (TTX) reduced the frequency of spontaneous EPSCs by 49.6 ± 4.3% and 61.8 ± 6.2% in the hippocampal and ATL samples, respectively. The magnitude of reduction caused by TTX with respect to non-seizure controls was significantly higher in the ATL samples than in the hippocampal samples. The magnitude of the change in the expression of the NR2A subunit of the NMDA receptors also varied in these two regions. Thus, the mechanism of hyperexcitabilty mediated by glutamatergic network reorganization in the hippocampal region is different from that in the ATL region of patients with HS, suggesting two independent resting-state networks at the cellular level. Taken together, these findings will improve the understanding of the broadly distributed resting-state networks in HS.